Sistematika Tinjauan Pustaka Pemikiran As-Syaibani: Implementasi Al-Kasb (Kerja) di Zaman Kontemporer - Fuja Dastiana; Hulwati Hulwati; Meirison Meirison (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This study aims to systematically examine Muhammad bin al-Hasan as-Syaibani’s thought on the concept of al-kasb (work) and its relevance in the contemporary economic context, particularly in Islamic economic and banking practices. The research employs a Systematic Literature Review (SLR) method using the PRISMA approach to analyze literature related to al-kasb, Islamic work ethics, and their application in modern economic systems. The findings indicate that al-kasb, according to As-Syaibani, is not merely an economic activity but a moral and social obligation that emphasizes lawful work, justice, and social responsibility. In the contemporary era, the principles of al-kasb are reflected in Islamic banking practices through real-sector-based contracts such as mudarabah, musyarakah, murabahah, and ijarah, as well as in strengthening Islamic work ethics and entrepreneurship. Ethical values such as trustworthiness, honesty, and social responsibility serve as essential foundations for economic stability and equitable distribution of wealth. However, challenges remain in its implementation, particularly regarding public literacy and the optimization of productive, Sharia-compliant financing.